Women Workers in the Manufacturing Industry in Malaysia - Noor Azizah, Ahmad (1996)
The dissertation is concerned with the relationship between the manufacturing sector and female employment in Malaysia. The failure of the economy in the early 1960s to provide substantial employment opportunities shifted the government’s emphasis towards labour-intensive industrial development. Manufacturing became an important economic activity after the 1970s. Two interesting features of the Malaysian manufacturing industry; ethnic dimension and gender dimension especially in terms of job hierarchy are examined in this study. Findings indicate that these dimensions structure the overall participation of workers in the manufacturing industry. The shift of the government policy has resulted in the increase of female participation in the formal sector of the economy compared with the previous years. This study then strives to investigate why multinational corporations prefer female to male workers and most importantly why female workers are relegated to the lower job hierarchy. In terms of ethnic dimension, the shift to the labour-intensive industry and the launch of the New Economic Policy not only resulted in the increase of Malay women employment but also the relative decrease of Chinese women employment in this sector.